A calcined clay fixed bed adsorption studies for the removal of heavy metals from aqueous solutions. (1st January 2021) - Khalfa, Leila; Sdiri, Ali; Bagane, Mohamed; Cervera, Maria Luisa
Abstract: A natural clay material from southern Tunisia was used as a low cost sorbent in a column-wise removal of metal pollutants. This is fundamentally important for a sustainable wastewater treatment strategy. This work has been performed within the framework of a project aiming to the valorization of natural geomaterials, from Tunisia, in several environmental applications. Column adsorption experiments were carried out for a better production of cleaner effluents and further understanding of the main mechanisms involved in the removal process, through a dynamic methodology, that would allow an industrial scale treatment. A calcined clay sample was used as an adsorbent for the removal of Pb(II), Cr(VI) and Cd(II) from aqueous solution. Lead removal, in presence of copper and zinc, was also studied. The effect of various parameters including bed height (2.0, 4.0 and 6.0 cm), flow rate (3, 5.8 and 9 mL/min) and influent metal ion concentrations (50, 100 and 150 mg/L) were investigated at an influent pH of 6. It was found that the exhaustion time increased with the increase of bed depth, the decrease of flow rate and initial concentration. Bohart -Adams, Thomas, Yoon–Nelson and Advection diffusion models were applied to the experimental data to predict the breakthrough curves for a better understanding of the main adsorption mechanisms. The assessment of the calcined clay performance may further explain the mechanism of metals-sorbent interaction at the water-clay interface. Thomas and Advection diffusion models were in good agreement with the experimental data. Column-wise packing of clays achieved excellent adsorption performances of metal ion in aqueous solution. The obtained results suggested a possible extension to the industrial scale of the fixed bed adsorption systems for cleaner water production, especially in the southern Tunisian districts where uncontrolled effluents discharge needs an immediate application of monitoring programs to for a sustainable improvement of water quality. Graphical abstract: Image 1 Highlights: Clay deposits of southern Tunisia effectively removed heavy metals in a column design. Competitive metals adsorption onto column-packed calcined clay were investigated. Yoon-Nelson and Thomas models are well suited for modeling the column-based adsorption. Metals capture by charred natural clay depended on column design and adsorption parameters. The studied material can be effectively used for cleaner water production.